(untitled) (JBN (Jurnal Bedah Nasional), 2026)
Background: Cryptorchidism (undescended testis, UDT) is the most common congenital anomaly of the male genitalia, defined by absence of one or both testes from the scrotum. Testes may arrest anywhere along the path of descent—most commonly within the inguinal canal—and, less often, in ectopic locations. Case Presentation: A healthy 18-month-old boy was brought by his mother with concern that the right testis had not descended. On examination, both hemiscrota were empty with no palpable testes. Ultrasonography demonstrated no intrascrotal testes; testicular shadows with homogeneous echotexture were identified within the inguinal canal bilaterally (right: 0.90 × 0.44 × 1.08 cm; left: 0.90 × 0.61 × 1.33 cm). Findings were consistent with bilateral inguinal-canal cryptorchidism. Conclusion: This case underscores the primacy of systematic physical examination—supported by targeted ultrasonography for localization—in evaluating suspected UDT. Given age >12 months and inguinal-canal location, orchiopexy is recommended, ideally before 18 months, to optimize testicular growth and reduce long-term risks (subfertility, malignancy, torsion). Hormonal therapy (e.g., human chorionic gonadotropin/hCG) may be considered in select circumstances but is generally less effective than surgery. Early referral and timely operative management remain the standard of care.